Nurses' role in consolidating longitudinal care for people with coronary artery disease - Marina Miotello; cintia koerich; Gabriela Marcellino de Melo Lanzoni; Alacoque Lorenzini Erdmann; Giovana Dorneles Callegaro Higashi (Universidade Federal de Santa Maria, 2020)
Aim: to understand how primary health care nurses experience the care of people with coronary artery disease in a longitudinal perspective. Method: qualitative study using semi-structured interviews to collect data and thematic analysis to handle them. It was attended by 16 nurses in the period between January and April 2016. Results: we raised the main category "Nurses' role in consolidating longitudinal care for people with CAD", underpinned by two subcategories addressing nurses' actions and factors interfering with the follow-up of the person with coronary artery disease. Final considerations: the follow-up of people with coronary artery disease in primary health care is based on welcoming, follow-up and conscious referral to other services of the health care network, as well as the effective communication among services of different technological densities, which can significantly contribute to the continuity and longitudinality of care.